TEXBOOK WRITING TRAINING FOR TEACHERSPelatihan Pembuatan Buku Ajar Untuk Guru - Dela Andriani; Hendra Aiyub; Rinaldi Mirsa; Rizki Alamsyah; Fauzan Farhan (Universitas Muhammadiyah Aceh, 2022)
Teachers are not only obliged to transfer the knowledge to their students. However, it is demanded to be more professional and more competent. One of thing can be done to improve the ability of the teachers in professional development is to increase the ability in writing a textbook. Based on the observations and the interviews with the teachers of SMA Pirak Timu, North Aceh District, there is still lack of understanding in writing a good textbook, as well as in using the applications that can be designed as learning media. For that reason, it is very important to have a training and assistance for teachers as an effort to develop the skills and creativity in writing textbook. This training had been done face to face (directly). After direct coaching, it is continued with assistance in writing textbook. With the existence of textbooks, teachers are expected to be able to prepare teaching materials which is sustainable, logical, contextual and up-to-date. Increasing teacher competence leads in increasing the student competence, so that learning objectives are expected to be achieved. The results obtained in this community service are a media publication, collaboration between Malikussaleh University and SMAN 1 Pirak Timu, and scientific journal publication. This work also has a positive impact on teachers to add scientific insight in writing textbooks to assist the learning process according to the condition and situations. Keywords: Textbook, learning media, Teachers